PENGGUNAAN PERINGATAN VISUAL DALAM PEMASARAN SOSIAL DAN RESIKO YANG DIPERSEPSIKAN KONSUMEN : PENGARUHNYA TERHADAP MINAT BELI KONSUMEN PRODUK ROKOK - Nuning Kristiani (Jurnal Bisnis, Manajemen, dan Akuntansi, 2017)
The research is aimed to find out the influence of the use of visual warning in social marketing and consumer perceptions of smoking risk toward the consumer buying interest. The independent variables in this study are visual warnings on cigarette packaging, cigarette packaging design, and consumer risk perception, and the dependent variable is the consumer buying interest. The research was conducted by choosing randomly the population of the whole smoker in Yogyakarta city as respondents using purposive sampling method.The number of samples used in this study were 120 respondents.The research resulted three important points. The first is the visual warning of the smoking hazard present in cigarette packaging has no influence the consumer buying interest, the second is the design of cigarette packaging influences the consumer buying interest, and the third isthe perceived risk of consumer influences the consumer buying interest.Keywords: Social Marketing, Visual Warning, Consumer Behavior, Packaging Design, Buying Interest